Effect of debittered fenugreek (Trigonella foenum‐graecum L.) flour addition on physical, nutritional, antioxidant, and sensory properties of wheat flour rusk. Issue 1 (1st December 2019) - Dhull, Sanju Bala; Punia, Sneh; Sandhu, Kawaljit Singh; Chawla, Prince; Kaur, Ramandeep; Singh, Ajay
Abstract: Fenugreek ( Trigonella foenum‐graecum ) is a unique legume crop having many pharmacological properties and health benefits attributed to its high soluble dietary fiber and phytochemicals. The main objective of this study was to evaluate selected functional and physical (color and pasting) properties of debittered fenugreek flour (DFF) and its addition on the nutritional value and acceptance of wheat flour rusk, prepared with 5%, 10%, 15%, and 20% DFF. The antioxidant potential and sensory attributes of DFF‐added rusks were also analyzed. The results revealed that with successive increase of DFF level, the nutritional, mineral, dietary fiber, and bioactive contents of the rusks were significantly ( p ≤ .05) enhanced. The progressive replacement at 0% to 20% level significantly ( p ≤ .05) improved the total phenolic content (157.5 to 455.8 mg GAE per 100 g), total flavonoid content (5.5 to 8.2 mg CE per 100 g), and antioxidant activity (20.4% to 45.5%). DFF incorporation significantly ( p ≤ .05) increased the water and oil absorption capacity, whereas peak viscosity, breakdown viscosity, final viscosity, setback viscosity, and peak temperature were decreased. The color of rusks became darker, the loaf weight and hardness increased, whereas loaf volume and specific loaf volume values were decreased with DFF addition. Sensory attributes of rusks were slightly affected with DFF incorporation, and rusks with 15% DFF were found most desirable with significantly ( p ≤ .05) enhanced nutritional, antioxidant, and sensory characteristics. The results of the present study demonstrated that incorporation of DFF at acceptable level could be achieved successfully for preparation of bakery product with enhanced nutritional and sensory quality.